KLASIFIKASI TEMA AYAT AL-QUR'AN PADA JUZ 30 MENGGUNAKAN TEXT MINING DAN ALGORITMA C4.5 BERBASIS WEB: CLASSIFICATION OF QUR'ANIC VERSE THEMES IN JUZ 30 USING TEXT MINING AND THE C4.5 ALGORITHM BASED ON WEB - Jihan Adila; Fadlisyah Fadlisyah; Said Fadlan Ansari (LPPM Universitas Abdurrab, 2025)
This study aims to develop a classification system for themes of the verses of the Qur'an in Juz 30 using the web-based C4.5 algorithm. The C4.5 algorithm has proven effective in the classification process, providing high accuracy in data processing. This system is designed to help users access and understand the themes contained in the verses automatically. By using text mining, this study allows processing and analysis of the text of the Qur'an, while the C4.5 algorithm is used to build a decision tree to classify themes such as morality, monotheism, and life after death. The data used consists of 38 themes that have been categorized based on the meaning and messages contained in the verses of Juz 30. The evaluation results of the model show an accuracy of 89.77%, with other evaluation metrics such as precision, recall, and F1-score showing satisfactory results. This system is implemented in the form of a web-based application, which allows users to select a theme and get related verses quickly and efficiently. With a simple and easy-to-use interface, this application makes it easy to search and understand themes in the Qur'an, and contributes to the development of understanding of Islamic teachings through modern technology.